The burden and determinants of HIV and sexually transmitted infections in a population-based sample of female sex workers in Goa, India. Issue 1 (6th August 2008) - Shahmanesh, M; Cowan, F; Wayal, S; Copas, A; Patel, V; Mabey, D
Abstract : Background: Interventions targeting sex workers are central to the National AIDS Control programme of India's third 5-year plan. Understanding the way in which societal and individual factors interact to shape sex workers' vulnerability would better inform interventions. Methods: 326 female sex workers, recruited throughout Goa using respondent-driven sampling, completed interviewer-administered questionnaires. Biological samples were tested for Trichomonas vaginalis, Neisseria gonorrhoea, Chlamydia trachomatis and antibodies to herpes simplex virus type 2 (HSV-2) and HIV. Multivariate analysis was used to define the determinants of HIV infection and any bacterial sexually transmitted infection (STI). Results: Infections were common, with 25.7% prevalence of HIV and 22.5% prevalence of bacterial STI; chlamydia 7.3%, gonorrhoea 8.9% and trichomonas 9.4%. Antibodies to HSV-2 were detected in 57.2% of women. STI were independently associated with factors reflecting gender disadvantage and disempowerment, namely young age, lack of schooling, no financial autonomy, deliberate self-harm, sexual abuse and sex work-related factors, such as having regular customers and working on the streets. Other factors associated with STI were Goan ethnicity, not having an intimate partner and being asymptomatic. Having knowledge about HIV and access to free STI services were associated with a lower likelihood of STI. HIV was independently associated with being Hindu, recent migration to Goa, lodge or brothel-based sex work and dysuria. Conclusion: Sex workers working in medium prevalence states of India are highly vulnerable to HIV and STI and need to be rapidly incorporated into existing interventions. Structural and gender-based determinants of HIV and STI are integral to HIV prevention strategies.